Analysis of Trade Receivable Control of Wahyu Putra Distributors - Zahro, Fatimataz; Warsono; Rahadjeng, Erna Retna (Universitas Muhammadiyah Malang, 2024)
This study aims to analyze the control of trade receivables at Wahyu Putra Distributors in 2019-2022. The analytical tools used are monitoring accounts receivable, assessing the Guttman scale, and identifying company policies and their implementation. This research shows that Wahyu Putra's distributors are less stringent in extending credit to customers. The credit standard implemented by the Wahyu Putra Distributor is only 2C, namely Character and Capacity and the credit requirements that are applied are too light. Monitoring of trade receivables such as accounts receivable turnover rate and the average day of collection of receivables between realization and the target is not in accordance with the results of the receivables aging schedule shows that many customers pay more than 30 days. The receivables collection policy that is applied is too mild and the company's policy in its implementation has been implemented according to operational standards. The conclusion of the study shows that the control of trade receivables in 2019-2022 at the Wahyu Putra Distributor is relatively ineffective, so it is necessary to make changes to the control of trade receivables in the company.